Teknologi Pesawat Tanpa Awak untuk Pemetaan Skala Detail Rencana Jaringan Pipa Sanitasi Komunal bagi Masyarakat Dusun Kepek 1, Kepek, Wonosari, Gunungkidul - Suharyadi Suharyadi; Yudhistira Tri Nurteisa (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
Human settlements can not be separated from the emergence of waste generated by human activity. Waste will give a negative efect on health and the environment if not handled and managed properly. Hamlet Kepek 1, Kepek, Wonosari have realized the impact that arises when household waste is not managed properly. For that, some residents have initiated a communal waste management and manufacture of communal sanitation pipelines. Conventionally, communal sanitary pipe network planning and data requires a huge cost, for it takes breakthrough of utilization of appropriate technology to facilitate the planning process and reduce the cost incurred.Utilization of small format aerial photographs resulting from the unmanned aircraf vehicle (UAV) used as an alternative technology in the planning communal sanitation pipelines. Analytical methods to create a map of the communal sanitation pipelines through least cost path analysis. Utilization of UAV technology is expected to make the planning of communal sanitary pipelines with good results and at afordable costs. Te result of small format aerial photography from unmanned aircraf vehicle (UAV) can be used to produce the spatial data with high resolution. Small format aerial photographs produced is then processed to obtain the orthophoto image and the image of Digital Surface Model (DSM). Both kinds of remote sensing image are then used as the main data to create maps of the communal sanitation pipelines. Te result of processing in the form of a map of communal sanitation pipelines in t Kepek 1 at low cost and appropriate technology.